Assistance in the establishment of BUMDes in Sonorejo Village, Candimulyo - Barkah Susanto; Ataj Amiratul Aida; Elifa Fenny Rahayu; Khofifa Lailatul Salamah; Lidya Sahira Atiqoh; Iffatul Farida (Universitas Muhammadiyah Magelang, 2022)
The Integrated Community Service (PPMT) activity regarding the establishment of BUMDes in Sonorejo Village, Candimulyo was carried out as an effort to develop investment and productivity by advancing the village economy, and facilitating community services to obtain welfare. This program was carried out with BUMDes administrators and village assistants. The method of implementing the program is carried out starting from socialization, assistance, monitoring and evaluation in the establishment of BUMDes. With this program, the establishment of BUMDes is expected to provide insight and experience and advance the village economy. The result of this program is the verification of all legal documents and the registration of the proposed BUMDes on the Ministry of Village website.